Einstein's universe - British Broadcasting Corporation (London : British Broadcasting Corporation, 1980)
Part 1-3 : This film honours the memory of an extraordinary man the German born mathematical physicist, Albert Einstein. His theory of relativity baffling earlier generations has come clear and vivid in an era of lacer beams and automatic clocks
Bahan rosak (Lupus)
Keywords: Einstein, Albert, -- 1879-1955; Physicists -- Biography